2015
DOI: 10.1016/j.stem.2015.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoid Regeneration from Gene-Corrected SCID-X1 Subject-Derived iPSCs

Abstract: Summary X-Linked severe combined immunodeficiency (SCID-X1) is a genetic disease that leaves newborns at high risk of serious infection and a predicted lifespan of less than one year in the absence of a matched bone marrow donor. The disease pathogenesis is due to mutations in the gene encoding the Interleukin-2 receptor gamma chain (IL-2Rγ) leading to a lack of functional lymphocytes. With the leukemogenic concerns of viral gene therapy there is a need to explore alternative therapeutic options. We have utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 31 publications
0
52
0
Order By: Relevance
“…A first report that defective T-cell differentiation associated with SCID can be modeled using patient-derived iPSCs has been provided by demonstrating an early arrest of T-cell development of cells carrying an IL2RG mutation, responsible for X-linked SCID, and rescue of T-cell differentiation by means of transcription activator-like effector nucleases-mediated gene editing. 24 Although recent work in the field adds to the understanding of PIDs in a human context, they were not aimed at elucidating the causality of the broad spectrum of clinical and immunologic phenotypes resulting from different mutations within the same gene. We reprogrammed dermal fibroblasts to generate iPSCs from patients with RAG1 mutations that resulted in different clinical and immunologic phenotypes (SCID and OS).…”
Section: Cd8mentioning
confidence: 99%
“…A first report that defective T-cell differentiation associated with SCID can be modeled using patient-derived iPSCs has been provided by demonstrating an early arrest of T-cell development of cells carrying an IL2RG mutation, responsible for X-linked SCID, and rescue of T-cell differentiation by means of transcription activator-like effector nucleases-mediated gene editing. 24 Although recent work in the field adds to the understanding of PIDs in a human context, they were not aimed at elucidating the causality of the broad spectrum of clinical and immunologic phenotypes resulting from different mutations within the same gene. We reprogrammed dermal fibroblasts to generate iPSCs from patients with RAG1 mutations that resulted in different clinical and immunologic phenotypes (SCID and OS).…”
Section: Cd8mentioning
confidence: 99%
“…Li et al, have successfully developed iPSCs from mouse mammary epithelial cells (ME-iPSCs) and re-differentiated them back into mammary epithelial cells (D-ME-iPSCs). Further transplantation of these D-ME-iPSCs into the fat pads of the mammary glands of nude mice result in the generation of mammary tree-like structures in vivo [53] Thus, this study envisions the use of iPSCs-derived tissue which could be used in parallel with gene editing tools to generate genetically corrected BRCA1/BRCA2 mammary cells. Besides, this gene editing platform has been successfully utilized to correct gene defect in iPSCs-derived from severe combined immunodeficiency (SCID) [53] and fanconi aneamia patient (hematological diseases) [54].…”
Section: Gene Correction In Ipscs and Autologous Transplantation: Prementioning
confidence: 99%
“…Similar to sickle cell disease and thalassemias, SCID patients can benefit from genetically corrected iPSCs that potentially may provide alternative sources for transplantation. Recently, three studies have been reported that iPSCs derived from different forms of SCID have been gene-corrected with TALEN and CRISPR endonucleases (Chang et al 2015; Howden et al 2015; Menon et al 2015). Menon and colleagues used the TALEN technology to correct a splice-site mutation in the interleukin-2 receptor gamma chain (IL-2Rγ) gene, which is required for the differentiation and maturation of the majority of lymphocytes.…”
Section: Corrections Of Disease-associated Genetic Mutations In Patiementioning
confidence: 99%